(untitled) (Bangladesh Journal of Zoology, 2012)
Impact of planting dates on Aphis gossypii Glover infestation and yields of eggplants was studied in the field. The aphid population was very low (4.75-31.05 aphids/plant) on the first planted crops. Yield of first planting dates were higher (1.56-3.58 kg/plant), however; aphid population on the successive late planting crops gradually increased and reached to peaks at third planting dates (15.51- 96.46 aphids/plant). Yield of eggplant gradually decreased on successive late planting crops and lowest yield recorded for third planting crops (1.06-1.88 kg/plant). DOI: http://dx.doi.org/10.3329/bjz.v39i2.10585 Bangladesh J. Zool. 39(2): 187-194, 2011